Motherthing - Hogarth, Ainslie (Vintage Books, 2022)
"A darkly funny domestic horror novel about a woman who must take drastic measures to save her husband and herself from the vengeful ghost of her mother-in-law. Abby Lamb has done it. She's found the Great Good in her husband, Ralph, and together they will start a family and put all the darkness in her childhood to rest. But then the Lambs move in with Ralph's mother, Laura, whose depression has made it impossible for her to live on her own. She's venomous and cruel, especially to Abby, who has a complicated understanding of motherhood given the way her own, now-estranged, mother raised her. When Laura takes her own life, her ghost starts to haunt Abby and Ralph in very different ways. Ralph is plunged into depression, and Abby is being terrorized by a force intent on taking everything she loves away from her. With everything on the line, Abby must make the ultimate sacrifice in order to prove her adoration to Ralph and break Laura's hold on the family for good"--